La porte - Van Zeveren, Michel 1970- (École des Loisirs, 2008)
A young girl seeks a little privacy in the family bathroom
Keywords: Girls / Juvenile fiction; Bathrooms / Juvenile fiction; Families / Juvenile fiction; Privacy / Juvenile fiction; Swine / Juvenile fiction; French language materials; Badezimmer; Familie; Mädchen; Missachtung; Privatsphäre; Bilderbuch